(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
At the same time that information technologies are rapidly developing, communication and information exchange are also developing at a great speed. The role of communication tools in increasing the convenience of communication is incomparable. Because the quality of communication is closely related to the means of communication. Initially, communication was carried out only through wire connectors. These wires connected users to each other through communication centers, and thus communication between cities and countries was established.